Adaptive optimal control of prosumer energy storage system with renewable energy sources - D. V. Antonenkov; V. Z. Manusov; P. V. Matrenin; V. R. Kiushkina (Омский научный вестник)
The prosumer can use energy storage to enhance the benefits of electricity trading by transferring buy and sell points. Improving energy efficiency is not considered from the standpoint of the entire system, but from an individual prosumer and in conditions of difficult-to-predict wind power generation. This work aims to optimize the prosumer’s electrical complex by developing a method for adapting the base of heuristic rules of the prosumer control to its parameters and climatic conditions. A method for adaptation control rules using swarm intelligence algorithms is proposed. The computer simulation has shown that the use of swarm algorithms makes it possible to increase the economic efficiency of managing the prosumer’s energy storage system by 2–4 times compared to the control rules manually constructed by an expert. It is shown that the proposed method makes it possible to automate the construction of the base of control rules.